A review on the treatment of hyperlipidemia with Erchen Decoction - Xinyang Tian; Peiyu Liu; Ruolin Wang; Yawei Hou; Ying Zhou; Chunyan Wang; Guiju Zhang (Frontiers Media S.A., 2024)
Hyperlipidemia, commonly referred to as dyslipidemia, is characterized by elevated serum cholesterol and/or triglyceride levels. This condition contributes significantly to the high mortality rates associated with cardiovascular diseases, posing a serious threat to global health. Although statins remain the predominant pharmacological treatment for hyperlipidemia, their associated side effects have led to a growing interest in alternative therapeutic approaches. Traditional Chinese Medicine (TCM) is exploring these alternatives, with the Erchen Decoction (ECD) emerging as a promising candidate. This review aims to summarize current clinical research, elucidate the mechanisms of action, and assess the compatibility of ECD in the management of hyperlipidemia. By doing so, we hope to provide valuable insights and references for clinical practice and future research.